Is Job Stability Declining in Germany? Evidences from Count Data Models - Rainer Winkelmann; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 1998)
The macro evidence of increased adjustment pressure since the early seventies suggests that job mobility should have increased. Hence, retrospective and spell data from the German Socio-Economic Panel are combined in order to test the hypothesis that job stability for German workers declined between 1974 and 1994. Using count data regression models in which we control for labour market experience, various demographic factors, and occupation, we find that job stability did not decrease, but if anything increase, between 1974 and 1994. Our findings suggest that labour market inflexibility is an important factor in explaining the European unemployment problem.
Keywords: J6; 330; job mobility; labour market flexibility; count data models; Arbeitsmobilität; Arbeitsplatzsicherung; Schätzung; Deutschland